Behind the wheel: Addressing the truck driver shortage crisis in Malaysia - Hoh, Sze Ling; Ng, Sze Yao; Wong, Phoebe Mun Yee (2025)
The trucking industry is vital to Malaysia’s economy but faces a persistent driver shortage that threatens supply chain efficiency and sustainability. While widely studied globally, research in Malaysia remains limited. This study explores the key factors behind the shortage, its impacts on logistics firms, and possible mitigation strategies from the perspective of industry professionals. Using a qualitative approach with semi-structured interviews of top and middle-level managers, the study applies thematic analysis to draw findings, implications, and conclusions. Three themes were examined. Under the factor theme, sub-themes include shifting workforce demographics, poor working conditions, and challenges in entry and recruitment. The impact theme highlights operational disruptions and delays, financial pressures, reduced service quality, reputational damage, and road safety risks. The mitigation strategy theme focuses on government initiatives, technological advancements, and company practices. Findings show that the shortage is driven by an aging workforce, high entry barriers, negative job perceptions, and poor working conditions. This issue disrupts supply chains, raise costs, and reduce service quality. Proposed solutions highlight the need for government support through subsidies, training and policy reforms. They also emphasise the adoption of technologies such as fatigue detection and GPS systems, as well as company-led initiatives that focus on better pay, welfare benefits and professionalisation programs. Effectively addressing the shortage will require coordinated efforts across government, industry and technology.